Radiographic criteria in developmental dysplasia of the hip in late infancy, inter and intrareader agreement - Desiree Alam; Souheil Hallit; Joseph Mandour; Boutros El Tannoury; Anthony Hassoun; Patrick Sami Bou Haidar; Majd El Hajj Moussa; Jean-Claude Lahoud; Charbel Tawk; Fadi Hoyek (PLoS ONE, 2025)
Introduction Developmental Dysplasia of the hip (DDH) is a common pediatric disorder screened for by antero-posterior (AP) pelvic radiographs in infants aged between 4–9 months. We chose from the radiographic indicators commonly used in the diagnosis the acetabular index, the Shenton line and the ossification and symmetry of the femoral head to assess for their reliability and variability among readers. In addition, this study aimed to obtain the mean age of appearance of the ossification center of the femoral head in the Lebanese population. Methods 149 pelvic AP radiographs of children between 4 and 9 months of age were collected. The criteria were assessed by three experienced readers: one orthopedic surgery fellow resident, one first-year and one second-year orthopedic surgery residents twice separated by a three-month interval. Results The bivariate analyses found a difference in the right Acetabular angle and left Acetabular angle significantly in the first- and second-year resident with a p < 0.01. No significant difference was found when comparing the readings of each reader independently for the other variables or with the fellow. We found a significant difference p = 0.047 when comparing the readings of the first-year resident and the fellow of the right AI. Whereas the left AI readings revealed significant differences between the fellow and the second-year resident (p = 0.008) and between the first and second-year residents (p < 0.001). Inter and intrareader consistency was high for the Shenton line rupture and the appearance of the ossification center on the femoral head but none of the parameters proved sufficient to significantly be associated with an acetabular angle> 30°. The average age of ossification center appearance in the Lebanese population was determined to be 5.57 months, aligning with global averages. Conclusion These findings call for a diagnostic approach that integrates multiple parameters and focuses on the importance of standardized training to enhance the consistency of radiographic assessments. Further investigations should aim to establish more precise protocols and evaluate the diagnostic strength of individual parameters.